Percepção de corrupção e legitimidade democrática na América Latina - Almeida, Taílon Rodrigues (2025)
The main objective that guided the research in this thesis was to analyze the effect of the perception of corruption on the legitimacy of the democratic regime in Latin America. We sought to contribute to the political behavior literature by analyzing the relationship between corruption and democracy based on the multidimensional paradigm of legitimacy, whose important theoretical insight by Easton (1975) gave rise to significant advances in democratic theory. In this sense, we adopt the concept of legitimacy based on the theoretical and analytical sophistication proposed by Norris et al (1999) in relation to Easton's notion of a distinction between diffuse support and specific support, according to which the objects of support for the regime are structured in a relatively independent manner and at various levels. Although these objects of political support are correlated with each other, they vary independently and have different meanings for democratic stability, which helps us to understand the corrosive extent of corruption as perceived by citizens. We analyzed whether the increase in the perception of corruption is related to possible risks that compromise the survival of democracy, trust in its institutions, or the reputation of the governments. In this respect, the research covered 19 Latin American countries, considering the indicators of perceived corruption as the independent variables of interest and the dimensions of political support as the set of dependent variables. An important innovation in this debate is the distinction between the perception of corruption towards public officials (PCFP) and the perception of corruption towards politicians (PCP). Based on this distinction, made possible by the inclusion of questions about politicians and civil servants in the Americas Barometer, we identified substantially different associations between the two types of perceived corruption and support for the regime, with the PCP having the greatest corrosive effect. We then included contextual variables in the models in order to analyze the interactive effect of context. We pay special attention to the intervening role of the “democratic legacy” (LegDem), as theoretically formulated by Casalecchi (2018). There are important theoretical reasons to suppose that the democratic legacy plays a mediating role in the effect of perceived corruption on democracy, given the evidence between increased legacy and strengthened support for the diffuse dimension of democracy. Our results indicate that the effect, however, is different from what was expected, as the models show that citizens in countries with a greater legacy were less likely to support the regime when they perceived greater levels of corruption, especially political corruption. In addition to democratic legacy, we mobilized other contextual variables to test the interaction between perceiving corruption and supporting democracy, namely: quality of democracy, GDP per capita and economic growth. Our database included the Americas Barometer database, Latinobarometer, the Varieties of Democracy (V-Dem) project and the Economic Commission for Latin America and the Caribbean (ECLAC), from which we extracted the main economic indicators.